Peanut butter feeding induces oral tolerance in genetically diverse collaborative cross mice - Immormino, Robert M.; Smeekens, Johanna M.; Mathai, Priscilla I.; Kesselring, Janelle R.; Turner, Andrew V.; Kulis, Michael D.; Moran, Timothy P. (Frontiers in Allergy, 2023)
Background Early dietary introduction of peanut has shown efficacy in clinical trials and driven pediatric recommendations for early introduction of peanut to children with heightened allergy risk worldwide. Unfortunately, tolerance is not induced in every case, and a subset of patients are allergic prior to introduction. Here we assess peanut allergic sensitization and oral tolerance in genetically diverse mouse strains. Objective We aimed to determine whether environmental adjuvant-driven airway sensitization and oral tolerance to peanut could be induced in various genetically diverse mouse strains. Methods C57BL/6J and 12 Collaborative Cross (CC) mouse strains were fed regular chow or ad libitum peanut butter to induce tolerance. Tolerance was tested by attempting to sensitize mice via intratracheal exposure to peanut and lipopolysaccharide (LPS), followed by intraperitoneal peanut challenge. Peanut-specific immunoglobulins and peanut-induced anaphylaxis were assessed. Results Without oral peanut feeding, most CC strains (11/12) and C57BL/6J induced peanut-specific IgE and IgG1 following airway exposure to peanut and LPS. With oral peanut feeding none of the CC strains nor C57BL/6J mice became sensitized to peanut or experienced anaphylaxis following peanut challenge. Conclusion Allergic sensitization and oral tolerance to peanut can be achieved across a range of genetically diverse mice. Notably, the same strains that became allergic via airway sensitization were tolerized by feeding high doses of peanut butter before sensitization, suggesting that the order and route of peanut exposure are critical for determining the allergic fate.